2022
DOI: 10.1097/cad.0000000000001280
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of CXCL17 and GPR35 in endometrial carcinoma

Abstract: Endometrial carcinoma is one of the most common gynecologic malignancies. CXCL17-CXCR8 (GPR35) axis is reported to play an indispensability role in tumors. Our purpose is to screen possible prognostic and immune-related factors in endometrial carcinoma by detecting the mRNA and protein expression of CXCL17 and CXCR8. We use the qRT-PCR method to test the mRNA expression of CXCL17 and CXCR8 in 35 pairs of endometrial carcinoma and adjacent tissue. The protein expression of CXCL17 and CXCR8 in 30 cases of normal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Moreover, the JAG1–CD46 interaction was detected in only HSIL and not at other disease stages; this interaction has been reported to induce the differentiation of CD4+ T cells into Tregs, representing the emergence of immunoregulatory features. (4) As precancerous lesions progressed into CC, we discovered ligand–receptor interactions, including CXCL17–GPR35 and WNT7B–FZD1, which exerted protumour effects by stimulating cancer cell proliferation and migration 37–39 . In addition, we detected CEACAM5–CD1D interactions between HPV‐related CA cells and myeloid cells and CEACAM5–CD8A interactions between HPV‐related CA cells and CD8+ T cells.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, the JAG1–CD46 interaction was detected in only HSIL and not at other disease stages; this interaction has been reported to induce the differentiation of CD4+ T cells into Tregs, representing the emergence of immunoregulatory features. (4) As precancerous lesions progressed into CC, we discovered ligand–receptor interactions, including CXCL17–GPR35 and WNT7B–FZD1, which exerted protumour effects by stimulating cancer cell proliferation and migration 37–39 . In addition, we detected CEACAM5–CD1D interactions between HPV‐related CA cells and myeloid cells and CEACAM5–CD8A interactions between HPV‐related CA cells and CD8+ T cells.…”
Section: Resultsmentioning
confidence: 91%
“…(4) As precancerous lesions progressed into CC, we discovered ligand-receptor interactions, including CXCL17-GPR35 and WNT7B-FZD1, which exerted protumour effects by stimulating cancer cell proliferation and migration. [37][38][39] In addition, we detected CEACAM5-CD1D interactions between HPV-related CA cells and myeloid cells and CEACAM5-CD8A interactions between HPV-related CA cells and CD8+ T cells. Given that CEACAM5 expression is closely related to HPV DNA integration into the host genome, 40 we inferred that the above cellular crosstalk mediated tumour-associated antigen presentation and immune activation of CD8+ T cells.…”
Section: F I G U R E 5 Cell-cell Communication Among Epithelial T And...mentioning
confidence: 79%
“…It has been speculated that the expression of CXCL17 by tumor cells in CRC contributes to the metastasis and growth of these cells. A study on endometrial adenocarcinoma tissues demonstrated that CXCL17 levels were remarkably elevated, and there is a significant and positive correlation between the expression of CXCL17 and CXCR8 (Hao et al 2022).…”
Section: Role Of Cxcl17 In Human Malignanciesmentioning
confidence: 99%
“…Furthermore, the expression of CXCL17 and GPR35 were considered a prognostic factor for the overall survival of patients who have endometrial cancer. Although it was not examined the role of this axis in the development of endometrial carcinoma, it was postulated that the CXCL17/GPR35 axis might be related to immune system regulation in the tumor microenvironment (Hao et al, 2022).…”
Section: Cxcl17 Genomic Characterization Tissue Distribution Receptor...mentioning
confidence: 99%